Polypropylene composition as well as preparation method and application thereof
By introducing SEBS and ethylene-butene copolymers into polypropylene resins, a sea island structure is formed, and using high-white silicate-based fillers and sorbitol-based permeability enhancers, the polypropylene material is solved in automotive exterior parts. The lack of optical properties and low-temperature toughness has achieved high light transmittance, low shrinkage and good low-temperature toughness.
Patent Information
- Application Number
- CN202510068026.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2045-01-16
AI Technical Summary
When used in automotive exterior parts, it is difficult to meet the requirements of high light transmission, and it is prone to rapid embrittlement in low-temperature environments, and the low-temperature toughness and shrinkage are insufficient.
By introducing SEBS and ethylene-butene copolymers into the polypropylene resin matrix, a highly uniform dispersible island structural resin system is formed, and a high-white silicate-based filler and sorbitol-based permeability enhancer are selected for combination, and the coordinated improvement is achieved. The light transmittance, low temperature toughness and dimensional stability of the product.
It realizes the high light transmittance, low shrinkage and good low-temperature toughness of polypropylene materials, improves processing performance and use performance, and is suitable for the preparation of automotive exterior parts.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and in particular to a polypropylene composition and a preparation method and application thereof. Background Art
[0002] Polypropylene is widely used in the fields of automobiles, electronic products, and home appliances because of its ideal mechanical properties and processing properties. However, when polypropylene materials are used in the automotive field, especially in the preparation of automotive exterior parts, specific exterior parts require higher light transmittance to meet the use standards. For this reason, people generally introduce transmittance enhancers to improve the transparency of the product. However, the transmittance enhancement degree of these transmittance enhancers when used in small amounts is still difficult to meet the use requirements. In addition to increasing production costs, introducing large amounts may also cause other performance to be weakened.
[0003] On the other hand, the polypropylene substrate needs to have good processing performance and high dimensional stability during the preparation process of automotive exterior parts. At the same time, it should not become rapidly brittle in some low-temperature processing and use scenarios (such as sub-zero temperature environments). In other words, the product is required to have low shrinkage and sufficient low-temperature toughness. Summary of the invention
[0004] Based on the defects of the prior art, the purpose of the present invention is to provide a polypropylene composition. The product is prepared by introducing styrene-ethylene-butylene-styrene block copolymer (SEBS) and ethylene-butylene copolymer into a polypropylene resin matrix to form a highly uniformly dispersed sea island structure resin system, and selecting specific high-whiteness silicate fillers and sorbitol-based transmittance enhancers for compounding. Under the synergistic effect of the components, the product can not only achieve a higher light transmittance, but also has a low shrinkage rate, good low-temperature toughness, and excellent processing performance and performance.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is: A polypropylene composition comprising the following components in parts by weight: 55-75 parts of polypropylene resin, 10-35 parts of SEBS, 4-12 parts of ethylene-butene copolymer, 5-20 parts of silicate filler, 0.1-0.5 parts of permeability enhancer; The whiteness of the silicate filler is ≥94%; The permeation enhancer is a sorbitol-based permeation enhancer.
[0006] Preferably, the whiteness of the silicate filler is tested by direct testing using a whiteness meter.
[0007] The specific test method is to use the WGB-2A desktop whiteness meter produced by Shanghai Precision Instruments, put a light-shielding black tube on the measuring space in advance and adjust the zero value with the instrument zero adjustment potentiometer. After the instrument zero position is stable, remove the black tube; put the standard whiteness plate on it and adjust the standard whiteness value with the instrument calibration potentiometer to calibrate the instrument, and then remove the standard whiteness plate; measure the sample to be tested to determine the whiteness value.
[0008] SEBS is often used as a toughening agent in plastic products due to its good elasticity. In the technical solution of the present invention, SEBS is introduced into the polypropylene resin matrix as a synergistic component, which can not only improve the toughness of the product, but also improve the light transmittance of the product to a certain extent. However, the microscopic particle sizes of polypropylene resin and SEBS are not the same. After melting to form a composite, the uniformity of the two components is insufficient and they are prone to creep. Therefore, if there are only these two components in the matrix resin of the product, the shrinkage rate of the product is high and the toughness at low temperatures is also low. For this reason, in the technical solution of the present invention, a specific content of ethylene-butene copolymer is further introduced into the composite matrix formed by the above two resins as a synergistic component. Through the traction effect of the component on the SEBS particles, the uniformity of the product composite resin is increased to form a highly dispersed island structure. Under the joint action of the three, the dimensional stability and low-temperature toughness of the product can be significantly improved; if other types of toughening agents are used, similar effects cannot be achieved.
[0009] On the other hand, the dimensional stability of the product is related to the content of filler added. It is well known in the art that too much filler can improve the dimensional stability of the product and reduce the shrinkage rate, but the toughness of the product will be relatively reduced, and the compatibility of organic resin and inorganic filler will also be reduced. With the introduction of fillers, the light transmittance of the product will also be affected. Therefore, in the technical solution of the present invention, after the specific high-whiteness silicate filler is compounded with sorbitol-based transmittance enhancer as a transmittance enhancer and introduced at the same time, the shrinkage rate of the product is reduced, and due to the synergistic effect of SEBS and ethylene-butene copolymer, the low-temperature toughness of the product is higher than that of the filler-free composite resin product, and the light transmittance can be maintained at a high level. If other types of fillers are selected, such as the frequently used titanium fillers, even if the whiteness is high, it is still difficult to achieve the ideal light transmittance, and the light transmittance will be significantly reduced if the silicate filler with insufficient whiteness is used. Similarly, other types of transmittance enhancers cannot play an effective role in this system, and cannot take into account the light transmittance, shrinkage and low-temperature toughness performance of the product.
[0010] Preferably, the weight proportion of the polypropylene resin is 55 parts, 60 parts, 65 parts, 70 parts, 75 parts or any two of the range values, the weight proportion of the SEBS is 10 parts, 13 parts, 15 parts, 20 parts, 21 parts, 25 parts, 30 parts, 35 parts or any two of the range values, the weight proportion of the ethylene butene copolymer is 4 parts, 5 parts, 6 parts, 8 parts, 10 parts, 12 parts or any two of the range values, the weight proportion of the silicate filler is 5 parts, 6 parts, 8 parts, 10 parts, 15 parts, 18 parts, 20 parts or any two of the range values, and the weight proportion of the permeability enhancer is 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts or any two of the range values.
[0011] Preferably, the polypropylene composition comprises the following components in parts by weight: 60-65 parts of polypropylene resin, 15-20 parts of SEBS, 5-10 parts of ethylene-butene copolymer, 10-15 parts of silicate filler, and 0.1-0.5 parts of permeability enhancer.
[0012] Preferably, the mass content of the polypropylene resin in the polypropylene composition is ≥45wt%.
[0013] Preferably, the polypropylene resin has a melt mass flow rate of 1 to 100 g / 10 min at 230° C. and a load of 2.16 kg according to ISO 1133-2011.
[0014] More preferably, the melt mass flow rate of the polypropylene resin at 230° C. and a load of 2.16 kg is 30 to 60 g / 10 min.
[0015] Preferably, the weight average molecular weight of the SEBS is 20,000 to 120,000; More preferably, the weight average molecular weight of the SEBS is 30,000-50,000.
[0016] The test method for the weight average molecular weight of the SEBS is gel permeation chromatography test; The specific test method is: dissolve an appropriate amount of SEBS in tetrahydrofuran, filter the resulting solution with a 0.22μm filter membrane, and use a TDA302 gel permeation spectrometer produced by Viscotek, USA, to test the weight-average molecular weight. The detectors used are differential and laser scattering detectors, the eluent is tetrahydrofuran, the flow rate is 1.0 mL / min, the test temperature is 25°C, the mass concentration of the solution is 2-5 g / L, and the standard sample is polystyrene.
[0017] Preferably, the SEBS has a melt mass flow rate of 1 to 15 g / 10 min at 230° C. and a load of 2.16 kg according to ISO 1133-2011.
[0018] Preferably, the mass ratio of the SEBS to the ethylene-butene copolymer is (6:1) to (1:1).
[0019] Further preferably, the mass ratio of the SEBS to the ethylene-butene copolymer is (4:1) to (3:2).
[0020] SEBS and ethylene-butene copolymer are both common toughening agents in polypropylene-based composite materials, but their microscopic particle sizes are different, so their toughening effects are also different. In the technical solution of the present invention, the ratio of the two has a certain influence on the light transmittance, low-temperature toughness and shrinkage of the product. Within the above preferred range, the comprehensive performance of the product is better.
[0021] Preferably, the weight average molecular weight of the ethylene-butene copolymer is 100,000 to 300,000; The weight average molecular weight of the ethylene-butene copolymer is tested by gel permeation chromatography. The testing method and steps of the ethylene-butene copolymer are the same as those of SEBS.
[0022] More preferably, the weight average molecular weight of the ethylene-butene copolymer is 150,000-250,000.
[0023] As mentioned above, ethylene-butene copolymer has multiple functions in the product, and its weight-average molecular weight also has a certain influence on the light transmittance and low-temperature toughness of the product. Within the above preferred range, the light transmittance and low-temperature toughness of the product can reach a higher level.
[0024] Preferably, the components of the polypropylene composition further include 0.5 to 1.5 parts of ethylene-octene copolymer.
[0025] Preferably, the weight average molecular weight of the ethylene-octene copolymer is 150,000-200,000.
[0026] In polypropylene compositions, ethylene-octene copolymers are more commonly used as compound toughening synergists than ethylene-butene copolymers. The toughness enhancement effect of this component on the product is not much different from that of ethylene-butene copolymers. However, in the product system described in the present invention, after ethylene-octene copolymers are used instead of ethylene-butene copolymers, the light transmittance of the product will be significantly reduced, and the standard performance cannot be achieved. On the basis of the composite system of polypropylene, SEBS, and ethylene-butene copolymers, ethylene-octene copolymers are further introduced for compounding, which can not only ensure that the light transmittance of the product will not decrease significantly, but also further improve the low-temperature toughness of the product and reduce the shrinkage rate, and the comprehensive performance of the product is better.
[0027] Preferably, the silicate filler includes at least one of silicate and aluminosilicate; More preferably, the silicate filler is at least one of talc powder, glass fiber powder, mica powder and quartz powder.
[0028] More preferably, the average particle size of the mica and / or talc and / or quartz powder is 8-16 μm.
[0029] More preferably, the glass fiber powder has an average diameter of 10-13 μm and an average length of 20-50 μm.
[0030] More preferably, the average length of the glass fiber powder is 20-30 μm.
[0031] The average particle size of mica and / or talc and / or quartz powder in the silicate filler of the present invention is determined by testing with a laser particle size analyzer with reference to GB / T19077-2016.
[0032] The average length and average diameter of the glass fiber powder in the silicate filler of the present invention are confirmed by the following method: the glass fiber powder is dispersed in water, and after ultrasonic oscillation treatment, the average length and average diameter are statistically confirmed under a second dimension using an optical microscope.
[0033] Preferably, in the polypropylene composition, the retained average particle size of the silicate filler is 4 to 15 μm.
[0034] The retained average particle size of the silicate filler in the polypropylene composition of the present invention is the average particle size of the silicate filler retained in the product after the specified polypropylene composition is melt-extruded and granulated.
[0035] Preferably, in the polypropylene composition, the retained average particle size of mica and / or talc and / or quartz powder is 4-10 μm.
[0036] Preferably, in the polypropylene composition, the retained average particle size of the glass fiber powder is 10-15 μm.
[0037] The test method for the retained average particle size of the silicate filler of the present invention is: calcining the polypropylene composition at 800° C. for 30 minutes in an air atmosphere, sieving the ash, and then testing and confirming it with a laser particle size analyzer with reference to the laser diffraction method of particle size distribution in GB / T 19077-2016.
[0038] Preferably, the sorbitol-based permeability enhancer is at least one of 1,2,3-trideoxy-4,6:5,7-bis-O-[(4-propylphenyl)methylene]-nonanol, 1,3:2,4-di(3,4-dimethylbenzylidene)-D-sorbitol, diphenylmethylene sorbitol, and di(p-methyldiphenylmethylene) sorbitol.
[0039] Preferably, the components of the polypropylene composition also include 0.1 to 1 part of an antioxidant and 0.1 to 1 part of a light stabilizer.
[0040] More preferably, the antioxidant is at least one of a hindered phenol antioxidant, a phosphite antioxidant, and a thioester antioxidant.
[0041] More preferably, the antioxidant is a mixture of a hindered phenol antioxidant and a phosphite antioxidant, and the mass ratio of the two is (0.8-1.2): (0.8-1.2).
[0042] More preferably, the light stabilizer is a hindered amine light stabilizer.
[0043] Preferably, the components of the polypropylene composition also include 0.1 to 3 parts of a processing aid.
[0044] More preferably, the processing aid includes at least one of an antistatic agent, a lubricant, an antibacterial agent, and a colorant.
[0045] It should be noted that the components of the polypropylene composition of the present invention may include, but are not limited to, the above-mentioned processing aids according to actual needs. Under the premise of not affecting the transmittance, shrinkage and low-temperature toughness of the polypropylene composition, those skilled in the art may select various processing aids to give the product other performance effects. For example, in order to give the product antistatic properties to achieve safety in the automotive field, an appropriate amount of antistatic agent may be added, and in order to increase the processing efficiency and demoulding effect of the product, an appropriate lubricant may be introduced into the product, etc.
[0046] Another object of the present invention is to provide a method for preparing the polypropylene composition, comprising the following steps: The components are mixed uniformly and then melt-extruded and granulated in a screw extruder to obtain the polypropylene composition.
[0047] Preferably, when the components are melt-extruded, the temperature zones of the screw extruder are set to 170-190°C in zone 1, 170-190°C in zone 2, 190-210°C in zone 3, 190-210°C in zone 4, 190-210°C in zone 5, 200-220°C in zone 6, 200-220°C in zone 7, 200-220°C in zone 8, 200-220°C in zone 9, and 200-220°C in zone 10, the screw speed is 350-450rpm, and the screw aspect ratio is (40-50):1.
[0048] The preparation method of the polypropylene composition of the present invention is simple to operate, has small requirements on equipment, and can realize industrial-scale production.
[0049] Another object of the present invention is to provide application of the polypropylene composition in the preparation of automobile decorative parts.
[0050] Preferably, the automobile decorative parts include at least one of an integrated luminous front face, a luminous tailgate back panel, a luminous door panel, a luminous fender, a luminous trim, and an intelligent control panel.
[0051] Another object of the present invention is to provide an automobile decorative part comprising the polypropylene composition of the present invention.
[0052] The polypropylene composition of the present invention has an ideal light transmission effect, and can achieve extremely low shrinkage and low-temperature toughness in a thinner size, and has excellent processing performance and use performance, and is very suitable for preparing the above-mentioned automotive decorative parts with relevant requirements.
[0053] The beneficial effect of the present invention is that the present invention provides a polypropylene composition, which is formed by introducing styrene-ethylene-butylene-styrene block copolymer (SEBS) and ethylene-butylene copolymer into a polypropylene resin matrix to form a highly uniformly dispersed sea island structure resin system, and simultaneously selecting specific high-whiteness silicate fillers and sorbitol-based transmittance enhancers for compounding. Under the synergistic effect of the components, the product can not only achieve a higher light transmittance, but also has a low shrinkage rate, good low-temperature toughness, and excellent processing performance and use performance. DETAILED DESCRIPTION
[0054] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used common reagents and instruments.
[0055] Embodiments 1 to 18 An embodiment of a polypropylene composition and a preparation method and application thereof according to the present invention, the components of the polypropylene composition are shown in Table 1.
[0056] The method for preparing the polypropylene composition comprises the following steps: The components are mixed uniformly and then melt-extruded and granulated in a screw extruder to obtain the polypropylene composition.
[0057] When the components are melt-extruded, the temperature zones of the screw extruder are set to 180°C in zone 1, 180°C in zone 2, 200°C in zone 3, 200°C in zone 4, 200°C in zone 5, 210°C in zone 6, 210°C in zone 7, 210°C in zone 8, 210°C in zone 9, and 210°C in zone 10, the screw speed is 400rpm, and the screw aspect ratio is 48:1.
[0058] Comparative Examples 1 to 10 The difference between the comparative examples and the embodiments is only in the types and proportions of components, as shown in Table 2.
[0059] Among the components described in each embodiment and comparative example, The polypropylene resin 1 is PPM60T produced by Zhenhai Refining and Chemical, and has a melt flow rate of 55 g / 10 min at 230° C. and a load of 2.16 kg; The polypropylene resin 2 is PP 320 powder produced by Sinopec Maoming, and the melt flow rate is 32 g / 10 min at 230° C. and 2.16 kg load; The SEBS 1 is SEBS 1643 produced by Kraton, USA, with a weight average molecular weight of 40,000; The SEBS 2 is SEBS1652 produced by Kraton, USA, with a weight average molecular weight of 35,000; The SBS is SBS1153 produced by Kraton, USA, with a weight average molecular weight of 40,000; The ABS is ABS KF730 produced by Kingfa Science & Technology, with a weight average molecular weight of 55,000; The SBR is SBR1605 produced by Dow Chemical, with a weight average molecular weight of 55,000; The ethylene-butene copolymer 1 is POE 7457 produced by Dow Chemical, with a weight average molecular weight of 170,000; The ethylene-butene copolymer 2 is POE 7447 produced by Dow Chemical, with a weight average molecular weight of 160,000; The ethylene-butene copolymer 3 is POE 7467 produced by Dow Chemical, with a weight average molecular weight of 240,000; The ethylene-butene copolymer 4 is POE9807 produced by Dow Chemical, with a weight average molecular weight of 110,000; The ethylene-butene copolymer 5 is POE 7367 produced by Dow Chemical, with a weight average molecular weight of 280,000; The ethylene-octene copolymer is POE 8842 produced by Dow Chemical, with a weight average molecular weight of 180,000; The glass fiber powder is MF7904 produced by Taishan Fiberglass, with an average diameter of 12 μm, an average length of 25 μm, and a whiteness of 94%; The mica powder is W-600 produced by Huajing Mica, and after screening, the average particle size is 15 μm and the whiteness is 94%; The quartz powder is produced by Wuhan Jiyesheng, and after screening, the average particle size is 12μm and the whiteness is 94%; The talcum powder 1 is BHS1851 produced by Xufeng Powder, with an average particle size of 15 μm and a whiteness of 94% after screening; The talcum powder 2 is 1250 talcum powder produced by Lingshou County Chengnuo Mineral Products Co., Ltd., with an average particle size of 12 μm and a whiteness of 90% after screening; The montmorillonite is I.3PS produced by NANOCOR in the United States, with an average particle size of 10 μm and a whiteness of 85%; The titanium dioxide Chemours produces TS1511, with a whiteness of 95%; The permeability enhancer 1 is NX8000K produced by Milliken, a sorbitol-based permeability enhancer; 1,2,3-trideoxy-4,6:5,7-bis-O-[(4-propylphenyl)methylene]-nonanol; The permeation enhancer 2 is Millad3988 produced by Milliken, a sorbitol permeation enhancer, 1,3:2,4-di(3,4-dimethylbenzylidene)-D-sorbitol; The permeability enhancer 3 is NA-21 produced by Aidico, a metal phosphate; The permeability enhancer 4 is sodium benzoate produced by Shanxi Chemical Research Institute; The antioxidant is a mixture of a commercially available hindered phenol antioxidant and a phosphite antioxidant in a mass ratio of 1:1; The light stabilizer is a commercially available hindered amine light stabilizer.
[0060] Unless otherwise specified, the components and raw materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.
[0061] The test method for the retained average particle size of the filler in each product in the embodiments and comparative examples is as follows: each product is calcined at 800° C. for 30 min in air, and then ash is sieved, and the particle size distribution is confirmed by laser diffraction method using a laser particle size analyzer with reference to GB / T 19077-2016.
[0062] Table 1 Table 2 In order to verify the performance of the polypropylene composition of the present invention, the products prepared in each embodiment and comparative example were subjected to the following performance tests, and the specific steps are as follows: (1) Light transmittance test: Each product was injection molded into a 100*100*3mm test square plate, and then tested according to GB 2410-2008; (2) Low temperature toughness test: tested according to ISO 180-2019, test temperature -30°C, type A notch; (3) Shrinkage test: Each product was injection molded into a 200*200*1mm test square plate and left to stand at room temperature for 24 hours. The length of the square plate was then tested and recorded as Amm. The shrinkage rate of the product was calculated as: 100%×(200-A) / 200.
[0063] The test results are shown in Tables 3 and 4.
[0064] Table 3 Table 4 As can be seen from Tables 3 and 4, the polypropylene composition of the present invention is based on the introduction of SEBS and ethylene-butene copolymer into the base resin to form a highly dispersed sea island structure system, and is matched with special fillers and transmittance enhancers, so that the product not only has ideal light transmittance, with a light transmittance of 60% or more, but also has a low shrinkage of 1.1% or less in a thin size, high low-temperature toughness, and a notched impact strength of at least 5KJ / m at -30°C. 2, and the comprehensive performance is excellent. According to Examples 1 and 3 to 5, it can be seen that the compounding ratio of SEBS and ethylene-butene copolymer forming the sea island structure has an impact on the various properties of the product. As the proportion of SEBS increases, the low-temperature toughness and dimensional stability of the product are improved, and when the ratio of the two is in the range of (4:1) to (3:2), the product can achieve a higher light transmittance. On the other hand, the molecular weight of the ethylene-butene copolymer also affects its dispersibility in the product and the increase in the performance of the product. As can be seen from Examples 1 and 8 to 11, the molecular weight of the ethylene-butene copolymer increases, and the light transmittance, low-temperature toughness and dimensional stability of the product are changed. When the weight-average molecular weight of the ethylene-butene copolymer is maintained in the range of 150,000 to 250,000, the comprehensive performance of the product is better. At the same time, if a portion of the ethylene-octene copolymer is introduced into the product system, as shown in Examples 12 to 14, the low-temperature toughness of the product can be further improved and the shrinkage rate of the product can be reduced while maintaining a high light transmittance.
[0065] In contrast, in the product of Comparative Example 1, only a single ethylene-butene copolymer is introduced into the base resin, and no resin sea island structure is formed, so the dimensional stability cannot be guaranteed, and the product with a single ethylene-butene copolymer compound has a low light transmittance. If the SEBS in the product is replaced with other types of reinforcing resins frequently used by technicians in this field, as shown in Comparative Examples 2 to 4, not only the light transmittance of the product cannot reach the expected level, but even the low-temperature toughness is also low. The notched impact strength of the product of Comparative Example 4 at -30°C is only 4.5 KJ / m 2 ; At the same time, in the technical solution of the present application, the ethylene copolymer with SBES must be an ethylene-butene copolymer. If it is replaced with an ethylene-butene copolymer, as shown in Comparative Example 5, the light transmittance of the product is extremely low. Although the size and type of the fillers used in the products of Comparative Examples 6 and 7 are close to those of the embodiment products, their whiteness is insufficient; although the fillers used in the products of Comparative Example 8 have a higher whiteness, they are not silicate fillers. The light transmittances of the three products do not meet the use requirements, and the low-temperature toughness of the product of Comparative Example 9 is also low. In the products of Comparative Examples 9 and 10, the transmittance enhancer is replaced with other types not specified by the present invention. In addition to the reduction in light transmittance, the low-temperature toughness and dimensional stability of the product are also difficult to meet the standards, indicating that in the products described in the present invention, the transmittance enhancer not only affects the light transmittance of the product, but also has a great influence on the dispersion and shrinkage of the product filler.
[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A polypropylene composition, characterized in that The composition comprises the following components in parts by weight: 55-75 parts of polypropylene resin, 10-35 parts of SEBS, 4-12 parts of ethylene-butene copolymer, 5-20 parts of silicate filler, 0.1-0.5 parts of permeability enhancer; The whiteness of the silicate filler is ≥94%; The permeation enhancer is a sorbitol-based permeation enhancer.
2. The polypropylene composition according to claim 1, characterized in that The polypropylene resin has a melt mass flow rate of 1 to 100 g / 10 min at 230° C. and a load of 2.16 kg according to ISO1133-2011.
3. The polypropylene composition according to claim 1, characterized in that The weight average molecular weight of the SEBS is 20,000-120,000.
4. The polypropylene composition according to claim 1, characterized in that The mass ratio of the SEBS to the ethylene-butene copolymer is (6:1) to (1:1).
5. The polypropylene composition according to claim 1, characterized in that The weight average molecular weight of the ethylene-butene copolymer is 100,000-300,000.
6. The polypropylene composition according to claim 1, characterized in that The components of the polypropylene composition also include 0.5 to 1.5 parts of ethylene-octene copolymer.
7. The polypropylene composition according to claim 1, characterized in that The silicate filler includes at least one of silicate and aluminosilicate.
8. The polypropylene composition according to claim 7, characterized in that The silicate filler is at least one of talcum powder, glass fiber powder, mica powder and quartz powder.
9. The polypropylene composition according to claim 8, characterized in that The average particle size of the mica and / or talc powder and / or quartz powder is 8-16 μm; the average diameter of the glass fiber powder is 10-13 μm, and the average length is 20-50 μm.
10. The polypropylene composition according to claim 1, characterized in that The components of the polypropylene composition also include 0.1 to 1 part of an antioxidant and 0.1 to 1 part of a light stabilizer; the antioxidant is at least one of a hindered phenol antioxidant, a phosphite antioxidant, and a thioester antioxidant; and the light stabilizer is a hindered amine light stabilizer.
11. The method for preparing the polypropylene composition according to any one of claims 1 to 10, characterized in that: The following steps are involved: The components are mixed uniformly and then melt-extruded and granulated in a screw extruder to obtain the polypropylene composition.
12. Use of the polypropylene composition according to any one of claims 1 to 10 in the preparation of automotive decorative parts.
13. The use according to claim 12, characterized in that The automobile decorative parts include at least one of an integrated luminous front face, a luminous tailgate back panel, a luminous door panel, a luminous fender, a luminous trim, and an intelligent control panel.
14. An automobile decorative component, characterized in that: The invention comprises the polypropylene composition according to any one of claims 1 to 10.
Citation Information
Patent Citations
A polypropylene composition, a method of producing the same, and articles made therefrom
CN101842434A
Low-gloss, soft-touch and non-woven fabric type polypropylene composite material as well as preparation method and application thereof
CN112625358A
Uniform light-transmitting polypropylene composite material as well as preparation method and application thereof
CN115197501A
High-weather-resistance transparent polypropylene automobile exterior trimming part and preparation method thereof
CN116496533A
High-scratch-resistance and light-transmitting polypropylene material as well as preparation method and application thereof
CN117126493A
Cited By
Polypropylene composition, and preparation method therefor and use thereof
WO2026152695A1
Polypropylene composition, and preparation method therefor and use thereof
WO2026152696A1